Development of a carbon nanofiber-attached flexible piezoelectric nanocomposite towards self-powered wearable devices. (2022) - Singh Panwar, Lokesh; Panwar, Varij
Abstract: The flexible piezoelectric nanocomposite (PNC) has the tremendous opportunity in wearable and foldable devices for healthcare detection, artificial skin, human body motion, and robotics applications. The aim of this paper was to develop the polymer based piezoelectric nanocomposite using cast solution method, the carbon nanofiber (CNF) was mixed with poly(vinylidenefluoride) (PVDF) polymer as a solvent, to make a series of flexible piezoelectric nanocomposite (PNC) out of PVDF/CNF and investigate their dielectric characteristics across a frequency range of 20 Hz to 10 MHz. Moreover, the piezoelectric performance of PNCs is examined by bending machine with sufficient bending cycles. The dielectric properties of PNCs were analyzed using the impedance analyzer for the varying wt% of CNF. It was discovered that the 2 %wt CNF based PNC showed excellent dielectric properties and maximum piezoelectric voltage of 0.62 V at bending strain of 0.009. These fabricated PNCs can be used for piezoelectric nanogenerator for self-powered and wearable sensors.